Определение зенитных тропосферных задержек в ГНСС-сети базовых станций - Лукьянов, А. М.; Гринченко, Е. В.; Галевич, М. Н.; Лукьянова, О. А. (ХНУРЭ, 2011)
Algorithm determination of the zenithal troposphere delays value on information of network of the base GNSS-stations is examined. Results of the experimental verification efficiency of the offered algorithms are presented.
Keywords: распространение радиосигналов; коэффициент рефракции; тропосферные задержки сигналов